Calculation of Nutritional Composition and "Growol" Calories in Micro and Medium Enterprises (MSMEs) in Kulon Progo - Kusumo, Mahendro Prasetyo (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
Yogyakarta Province is ranked second with the highest prevalence of Diabetes Mellitus (DM) in Indonesia. Choosing the right food for someone with DM is incredibly significant as it directly impacts their blood sugar levels. The aim of this community service is to increase the knowledge of MSME entrepreneurs and the community about the nutritional and calorie content of Growol which can be an alternative food to replace rice for DM patients. The method chosen to overcome this problem is through service learning. This community service was carried out in Hargomulyo Village, Kokap District, Kulon Progro Regency. This community service activity has been proven to increase the knowledge of MSME entrepreneurs and the community in recognizing nutritional content and how to calculate food calories. MSME entrepreneurs are also able to utilize innovation and technology to market and grow